Comercializarea produselor medicinale veterinare la distanță (on-line) și prin farmaciile comunitare - Marius M. Bunea (Medicamentul Veterinar)
In this PPT, a presentation is made about the sale of veterinary medicinal products at a distance (online) and through community pharmacies in the light of the provisions of Regulation (EU) 2019/6 regarding the online sale of veterinary medicinal products and Romanian legislation. In Romania, remote retail (on-line) sales of veterinary medicinal products can be carried out: only through veterinary pharmacies authorized by a sanitary-veterinarian and veterinary pharmaceutical points registered by a sanitary-veterinary, and only with veterinary medicinal products that are issued without a medical prescription veterinarian. Every economic operator who wants to carry out remote retail trade activities must send a notification to ANSVSA (according to the model provided in Annex 3.1 of Order of the President of ANSVSA no. 83/2014). After verification for compliance with the legislation in force, ANSVSA enters the operator in the list of retailers, who are allowed to sell veterinary medicinal products online.